Propuesta de Guía para la Implementación de la Norma ISO 9001:2015, en la Unidad Educativa Fiscomisional Mercedes de Jesús Molina, Año 2023 - Moreno Torres, Milagros Nathalia (2024)
This curricular integration project aimed to develop a guide proposal for implementing ISO 9001:2015 at the Fiscomisional Educational Unit Mercedes de Jesús Molina, located in the city of Loja. The purpose was to meet the needs of the institution's members and its users through the efficient performance of its management system. Achieving the objectives outlined in this research required the use of a qualitative approach and various methods, including deductive, analytical, and synthetic approaches. To further support the study, research techniques such as interviews, observation sheets, PESTEL analysis, AMOFHIT analysis, Stakeholders matrix, Tows matrix, and the software (Word) were employed. These techniques facilitated the initiation of a situational diagnosis to understand the context in which the institution was situated. Subsequently, all the gathered information was analyzed to develop a guide proposal that addressed the identified issues. This proposal was then discussed with the academic representative, fulfilling the overall objective. Through the application of the guide, it is expected that the Fiscomisional Educational Unit Mercedes de Jesús Molina will optimize the performance of its management system. This optimization will enable the institution to operate in an organized and efficient manner, effectively meeting the guidelines established by the Ministry of Education. Furthermore, this will contribute to enhancing the institution's reputation and prestige.